1987
DOI: 10.1093/nar/15.4.1819
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the streptomycinphosphotransferase and amidinotransferase genes fromStreptomyces griseus

Abstract: Genes for streptomycin phosphotransferase and inosamine-P-amidinotransferase from a streptomycin-producing Streptomyces griseus were cloned on a 3.8kb BamHI-SphI fragment in S. lividans using the multicopy cloning vector pIJ702. The nucleotide sequence of this 3.8kb fragment was determined and the coding sequences for the two genes were identified by comparison with the amino-terminal sequences of the two enzymes purified from S. lividans clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Recently, the sequence of an overlapping DNA fragment starting with the SphI site in position 1782 (Fig. 2), derived from the same gene cluster in an obviously related strain, S. griseus ISP2536, has been reported (12). The DNA sequences derived from the two strains differ in 56 out of 3838 bases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the sequence of an overlapping DNA fragment starting with the SphI site in position 1782 (Fig. 2), derived from the same gene cluster in an obviously related strain, S. griseus ISP2536, has been reported (12). The DNA sequences derived from the two strains differ in 56 out of 3838 bases.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the five genes and their products involved in SM resistance and production, phD (strA; APH (6)), strB (ADT), strC, strR, smi-67, and the gene complementing mutant SD-1, which all had been localized by their phenotypes on contiguous segments of DNA in S. griseus and closely related species (4,7,8,10,12), only two have been identified so far by DNA and polypeptide sequencing: the major resistance gene (aphD; 10,12), coding for the APH(6) enzyme, and a biosynthetic gene (strB; 7,12, this paper), coding for an aminocyclitol amidinotransferase (ADT). The use of the two open reading frames, ORF1 and ORF5, additionally found on the determined sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of mutants blocked in streptidine biosynthesis have subsequently provided independent support for the proposed enzymatic pathway (6,12,15). In related genetic studies (5,7,10,16,19), a streptomycin biosynthetic gene cluster has been found which contains genes coding for (i) streptomycin 6-kinase, originally detected as streptidine kinase activity with a biosynthetic function under certain conditions (30); (ii) amidinotransferase, the first pathway enzyme discovered (26); and (iii) several other putative biosynthetic and regulatory activities.The remarkable symmetry of the streptidine biosynthetic pathway led to my early speculation that gene duplication and subsequent divergence might have provided the additional enzymes required to synthesize the second guanidino group (20). It was soon recognized that such evolutionary speculation would be greatly strengthened if (i) evidence could be obtained for the existence of the postulated progenitor single guanidino pathway; (ii) corresponding reactions of the two analogous biosynthetic sequences responsible for streptidine synthesis could be shown to be catalyzed by different enzymes, with in some cases overlapping substrate specificities; and (iii) the predicted DNA and amino acid sequence homologies could be detected in both the progenitor and streptomycin producers.…”
mentioning
confidence: 99%
“…Studies of mutants blocked in streptidine biosynthesis have subsequently provided independent support for the proposed enzymatic pathway (6,12,15). In related genetic studies (5,7,10,16,19), a streptomycin biosynthetic gene cluster has been found which contains genes coding for (i) streptomycin 6-kinase, originally detected as streptidine kinase activity with a biosynthetic function under certain conditions (30); (ii) amidinotransferase, the first pathway enzyme discovered (26); and (iii) several other putative biosynthetic and regulatory activities.…”
mentioning
confidence: 99%